Empowerment of Youth for Rural Development - Garg, Ajay (Journal of Commerce and Trade, 2019)
The future of any country lies in its youth. Today’s youth are the most creative innovative, Tea-savvy and have the power to transform the nation to build more powerful and prosperous world. India has the world’s largest youth population a very favorable demographic profile with a median age of about 28 years which suggest that youth will make a significant contribution to the economic development and prosperity of the country. Classification-JEL : J 17, R 13